2022
DOI: 10.1590/1982-7849rac2022200377.en
|View full text |Cite
|
Sign up to set email alerts
|

Relacional: Easing the Crisis Effects in the Education Sector

Abstract: This teaching case addresses the need for change in Relacional’s business strategy, driven by the negative effects of the COVID-19 pandemic in the Brazilian educational sector in the first half of 2020. The startup is a software warehouse whose systems seek to solve specific problems of educational institutions, from basic to higher level, such as relationship, attraction, and retention of students. In the midst of a scenario of probable crisis in the sector, the partners seek business alternatives to assist e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%